Draft Eighth Five Year Plan 1990-95 Volume : VI General Areas Government of Assam - Planning Commission (Planning Commission, 1990)
During the Seventh plan, the activities under the scheme have strengthened. During the plan period, ten Food Inspectors and Five Regional Food Inspectors have been appointed as a measure of increase of enforcement staff. The Public Analyst Laboratory at Guwahati has been developed with the financial assistance of North Eastern Council.
Government of Assam, Planning and Development Department